Cardiac Myosin Binding Protein C Insufficiency Leads to Early Onset of Mechanical Dysfunction - Desjardins, Candida L. (2011)
BACKGROUND: Decreased expression of cardiac myosin binding protein C (cMyBPC) as a result of genetic mutations may contribute to the development of hypertrophic cardiomyopathy (HCM); however, the mechanisms that link cMyBPC expression and HCM development, especially contractile dysfunction, remain unclear. METHODS AND RESULTS: We evaluated cardiac mechanical function in vitro and in vivo in young mice (8–10 weeks of age) carrying no functional cMyBPC alleles (cMyBPC(−/−)) or 1 functional cMyBPC allele (cMyBPC(±)). Skinned myocardium isolated from cMyBPC(−/−) hearts displayed significant accelerations in stretch activation cross-bridge kinetics. Cardiac MRI studies revealed severely depressed in vivo left ventricular (LV) magnitude and rates of LV wall strain and torsion compared with wild-type (WT) mice. Heterozygous cMyBPC(±) hearts expressed 23±5% less cMyBPC than WT hearts but did not display overt hypertrophy. Skinned myocardium isolated from cMyBPC(±) hearts displayed small accelerations in the rate of stretch induced cross-bridge recruitment. MRI measurements revealed reductions in LV torsion and circumferential strain, as well reduced circumferential strain rates in early systole and diastole. CONCLUSIONS: Modest decreases in cMyBPC expression in the mouse heart result in early-onset subtle changes in cross-bridge kinetics and in vivo LV mechanical function, which could contribute to the development of HCM later in life.